Bounding information and media frontiers: short papers [de] SIACG 2002 - 1st Ibero-American Symposium in Computer Graphics - Santos, Próspero dos (2013)
This is the book of short papers of the 1st Ibero-American Symposium in Computer Graphics (SIACG) which was the first in a series of similar events organised every year, alternating between Europe and South America. Its mission is to foster transatlantic co-operation through the exchange of scholars, ideas, information and participation in joint projects between Computer Graphics communities in the Iberian Peninsula and Latin America.